EFEKTIVITAS PENYULUHAN DENGAN AUDIO VISUAL TERHADAP KEBERHASILAN TOILET TRAINING PADA ANAK UMUR 2-3 TAHUN DI BANJAR TAMAN PALEKAN BATUBULAN - Luh Putu Karsi Ekayani; Francisca Shanti Kusumaningsih; Putu Susy Natha Astini (Coping: Community of Publishing in Nursing, 2017)
Critical period in growing child is toddlers. According to psikoseksual theory, toddler is anal phase, they are to begin was able to control the defecate and urination. In this phase is the good time to teach children about toilet training. To teach children about toilet training can do with health education with an interesting media like audio visual. The purpose of this research is to know effectiveness of health education with audio visual against successful of toilet training in children two until three years at Taman Palekan hamlet. The study was used pre experimental design with one group pretest-posttest design. Sample was consisted of 25 children which selected by using total sampling technique. The data was collected by questionnaire before and after health education with audio visual. The result of this studi were increased success of toilet training a child who successfully category from 12% to 48%, is successful 68% to 44%, and did not success 20% to 8%. Based on Wilcoxon test p = 0.001 means p <0,05 so Ho is rejected. Based on these studies, health education with audio visual effectively to the success of children's toilet training.